Prevention of distal flap necrosis in a rat random skin flap model by gene electrotransfer delivering VEGF165 plasmid. (March 2014) - Basu, Gaurav; Downey, Harre; Guo, Siqi; Israel, Annelise; Asmar, Anthony; Hargrave, Barbara; Heller, Richard
Abstract Background Therapeutic delivery of angiogenic growth factors is a promising approach for treating ischemia observed in skin flaps and chronic wounds. Several studies have demonstrated that vascular endothelial growth factor (VEGF) helps mitigate skin flap necrosis by facilitating angiogenesis. The present study aimed to demonstrate an electrically‐mediated nonviral gene delivery approach using a non‐invasive multi‐electrode array (MEA) for effective treatment of ischemic skin flaps. Methods We used a standard random dorsal skin flap model in rats. The study aimed to determine the optimal treatment sites on the skin flap, optimal plasmid dose and timing of the treatment for preventing distal flap necrosis. Results We determined that two treatment sites on the ischemic flap with a plasmid dose of 50–100 µg per treatment site proved adequate to prevent > 95% flap necrosis, and that this was significantly better than the no treatment or injection only group. A 2‐day window was critical to deliver the VEGF to achieve flap survival and prevent necrosis. Histological examination demonstrated minimal electrotransfer associated tissue damage. Conclusions Our results demonstrate that MEA can be used as a non‐invasive physical gene delivery method for plasmid VEGF, resulting in a significant reduction of necrosis in ischemic wounds. We propose that this method could be translated into a potential therapeutic approach to deliver growth factors to prevent ischemia in cases of chronic wounds, burns and skin flap necrosis. Copyright © 2014 John Wiley & Sons, Ltd.